ANALISIS PENGARUH ASET DAERAH DAN BELANJA MODAL TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KORIDOR UTARA SELATAN PROVINSI JAWA TIMUR - Lu’lu’ul Husniatuz Zuhroh (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to determine the effect of Regional Assets and Capital Expenditures on Gross Regional Domestic Product in the corridor of North South East Java Province by considering the data that have been collected. The data used in this study is secondary data released by Directorate General of Fiscal Balance in APBD table, financial balance sheet and Gross Regional Domestic Product table issued by Central Bureau of Statistics (BPS). The variables in this study are Gross Regional Domestic Product, Regional Assets and Capital Expenditure, to determine the effect of independent variables on dependent variables using regression panel data analysis methods. The result of the research shows that the Regional Asset and Capital Expenditure have positive and significant impact to Gross Regional Domestic Product in North South Corridor East Java ProvinceKeywords : : assets, capital expenditure, Gross Regional Domestic Product